2011
DOI: 10.1074/jbc.m111.256149
|View full text |Cite
|
Sign up to set email alerts
|

The α1 Subunit EGL-19, the α2/δ Subunit UNC-36, and the β Subunit CCB-1 Underlie Voltage-dependent Calcium Currents in Caenorhabditis elegans Striated Muscle

Abstract: Background:The composition of voltage-gated calcium channels is important for function. Results: In C. elegans, calcium currents are altered in mutants of one main subunit (EGL-19) or the accessory subunits UNC-36 and CCB-1. Conclusion: Voltage-gated calcium channels of C. elegans striated muscles are composed of EGL-19, UNC-36, and CCB-1. Significance: C. elegans could be a new model to study the roles of accessory subunits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 46 publications
2
38
0
Order By: Relevance
“…Nemadipine treatment (10 µM) completely blocked voltage-activated EGL-19/CaV1 calcium current in body muscles (Fig. S1A–B), confirming that Nemadipine is an effective EGL-19 antagonist (Laine et al, 2011). …”
Section: Resultssupporting
confidence: 62%
“…Nemadipine treatment (10 µM) completely blocked voltage-activated EGL-19/CaV1 calcium current in body muscles (Fig. S1A–B), confirming that Nemadipine is an effective EGL-19 antagonist (Laine et al, 2011). …”
Section: Resultssupporting
confidence: 62%
“…Microdissection of C. elegans and electrophysiological methods were performed as described previously (Lainé et al, 2011). The resistance of recording pipettes ranged between 3 and 3.5 MU.…”
Section: Electrophysiologymentioning
confidence: 99%
“…R 200 , which represents the current fraction still present at the end of the pulse (Eqn 2), is higher in egl-19 (Lainé et al, 2011) and a recent study has also shown that the interaction between α 1 and α 2 -δ subunits is strong and that they are intimately associated at the plasma membrane (Cassidy et al, 2014). The expression of GFP:UNC-36 in unc-36 mutants rescued the locomotion phenotype and the Ca 2+ current defects observed in unc-36 mutants (Lainé et al, 2011;Zhan et al, 2014), so we assumed that the localization of the fusion protein matched that of endogenous channels. As previously described (Frøkjaer-Jensen et al, 2006), unc-36 staining was observed in most neuronal and muscle cells (Fig.…”
Section: Research Articlementioning
confidence: 99%
“…The fractional inactivation at the end of the pulse (R 200 ) and the time constant of activation (τ) were measured for the maximal current traces [at +20 mV for wild-type (N=15), +10 mV for egl-19(ad695) (N=15) and 0 mV for egl-19(n2368) (N=12)]. R 200 , which represents the current fraction still present at the end of the pulse (Eqn 2), is higher in egl-19 (Lainé et al, 2011) and a recent study has also shown that the interaction between α 1 and α 2 -δ subunits is strong and that they are intimately associated at the plasma membrane (Cassidy et al, 2014). The expression of GFP:UNC-36 in unc-36 mutants rescued the locomotion phenotype and the Ca 2+ current defects observed in unc-36 mutants (Lainé et al, 2011;Zhan et al, 2014), so we assumed that the localization of the fusion protein matched that of endogenous channels.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation